Inibitory effects of linalool on fungal pathogenicity of clinical isolates of Microsporum canis and Microsporum gypseum. Issue 6 (15th February 2017) - Silva, Kaltz V. S.; Lima, Maria I. O.; Cardoso, Gustavo N.; Santos, Aldeir S.; Silva, Gezaíldo S.; Pereira, Fillipe O.
Summary: In humans worldwide, Microsporum sp. is a frequent agent of dermatophytsosis. When considering the emergence of resistant fungi and the clinical relevance of dermatophytosis, terpene antifungal activity is of great interest. Linalool is a monoterpene alcohol with pharmacological properties. In this study, antifungal in vitro activity of linalool and ketoconazole (as a positive control) were evaluated against clinical isolates of M. canis and M. gypseum . The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of each drug were determined by broth microdilution. The effects of the drugs (1/2MIC, MIC, 2xMIC) on radial mycelial growth, conidial production and germination were analysed. The effect on the fungal cell membrane (release of intracellular material) was also investigated. Linalool (MIC: 128 μg/mL) and ketoconazole (MIC: 64 μg/mL) were effective in inhibiting all dermatophytes studied. The MFC values of linalool ranged between 128 and 256 μg/mL, whereas ketoconazole showed MFC values of from 64 to 256 μg/mL. Linalool (at MIC and 2xMIC) and ketoconazole (at 1/2MIC, MIC, 2xMIC) inhibited mycelial growth ( P  < 0.05). The drugs (1/2MIC, MIC, 2xMIC) were also active on conidiogenesis and conidia germination, causing complete inhibition ( P  < 0.05). Linalool caused leakage of intracellular material. Our study supports the use of linalool as a potential antifungal agent against M. canis and M. gypseum .